“Learning to Listen to Them and Ask the Right Questions.” Bennet Omalu, Scientific Objectivities, and the Witnessing of a Concussion Crisis - Hollin, Gregory (Frontiers in Sports and Active Living, 2021)
The death of American Football player Mike Webster has become foundational to narratives of sport's twenty-first century concussion crisis. Bennet Omalu, the neuropathologist who conducted Webster's autopsy and subsequently diagnosed Webster with Chronic Traumatic Encephalopathy (CTE), has, likewise, become a central figure in the concussion crisis. Indeed, it is frequently argued that there is something about Omalu in particular that made it possible for him to “witness” CTE when the disease entity had hitherto remained invisible to a great many medics and scientists. In this article, and drawing upon auto/biographies, I consider Omalu's self-described mode of scientific witnessing which purportedly allowed him to (re)discover CTE. I find Omalu's described objectivity to be shaped by three factors: First, the importance of “trained judgment” within which Omalu's scientific training is emphasized. Second, the infusion of religiosity within scientific practice. Third, a self-described position as an “outsider” to both football and American culture. Throughout this analysis, I pay attention not only to the ways in which Omalu's narratives depart from conventional depictions of scientific objectivity; I also note the similarities with particular bodies of social scientific work, most notably within a feminist “turn to care” in Science and Technology Studies (STS) and related standpoint epistemologies. Following these analyses, I argue that, first, Omalu's writing affords the dead a “response-ability” that is often absent within analyses of the concussion crisis and, second, that a focus upon diverse forms of objectivity, such as those described in Omalu's work, complements existing work into concussion science that has foregrounded scientific conflict of interest.